PROGRAM FOR ADOLESCENCE CORRECTION OF ADOLESCENTS WITH ADDICTIVE BEHAVIOR AND THE RESULT OF ITS IMPLEMENTATION - Trofimchuk V. V. (International Journal of Innovative Technologies in Social Science, 2020)
The article analyzes the results of the formative stage of the experiment on the implementation of a program to correct the aggression of adolescents with addictive behavior. The essence of aggression of adolescents with additive behavior, which is understood as an integrated set of personality traits of adolescence, which is manifested in destructive actions under the influence of any substances that change the mental state. Scientific approaches to the interpretation of aggression as a phenomenon (activity, axiological, motivational, behavioral, ethological, sociological, personal) are characterized. Based on the selected approaches, the content and structure of aggressiveness of adolescents with addictive behavior, which contains cognitive, motivational, affective, behavioral component, is determined. The main task of the article is to highlight the results and effectiveness of the program to correct the aggression of adolescents with addictive behavior. Diagnostic means of studying the levels of aggression of adolescents with additive behavior and its components are presented (test "Psychotropic substances", scale of search of impressions (M. Zuckerman), method "Diagnosis of hostility", method "Self-assessment of personality", method "Scale of emotional stability - instability G. Eisenko"; questionnaire" Are you prone to drug use?", A questionnaire to identify students with deviant behavior in the classroom). The content of the program of correction of aggression of adolescents with addictive behavior, consisting of three modules: "Knowledge of yourself and others", "Factors of addiction and manifestations of aggression of adolescents", "Strategies for overcoming aggression of adolescents with addictive behavior". The structure of training sessions of the program for correction of aggressiveness of adolescents with addictive behavior is described. The strategy of the formative stage of the experiment, in which 56 adolescents took part, is substantiated. The results of approbation of the program of correction of aggression of teenagers with addictive behavior, which proved its effectiveness, are presented. The proposed program was found to reduce the level of aggression in adolescents with addictive behavior.